Enhancing EFL Students' Recount Text Writing Performance: Challenges and Strategies in Indonesian Classroom Settings - Dian Novi Isroyana; M Saleh Yahya Himni (Saniya Institute, 2025)
The present study examines the writing performance of students in an English as a Foreign Language (EFL) classroom setting with regard to recount texts. Recount texts enable readers to gain insight into past events through the presentation of a series of events in a linear sequence. This study examines a phenomenon pertaining to students' writing performance of recount text in an EFL classroom setting. The objective of this study is to examine students' performance in the composition of study texts. This study employed a descriptive qualitative research design. The findings indicate that numerous challenges were encountered during the learning process, which negatively impacted the students' writing abilities. The students encountered difficulties in constructing sentences and conveying their ideas. The findings are presented below: One student demonstrated excellence, two students were classified as suitable, five students were placed in the fair category, and eight students were classified as less proficient. In light of these findings, the researcher asserts that students' writing performance in recount texts remains a point of improvement.